Somatotyping of Swiss team skialpinism athletes - Clijsen, R.; Taeymans, J.; Rinderer, S.; Hebbelinck, M.; Cabri, J. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
The aim of this study was to assess the somatotype (S) of Swiss Team Skialpinism (STS) athletes. Ten male and three female STS athletes participated in this study. Anthropometry was assessed following the ISAK guidelines. S was calculated using the Carter&Heath method (1990). References of other ski disciplines were used for comparison. A simple t-test procedure was used for analysis. Conclusion: Male and female Swiss Team Skialpinism athletes show ectomorphicmesomorph and endomorphic-mesomorph somatotypes respectively. Male STS athletes show significant lower mesomorphy levels than athletes of other ski disciplines. In the male group, mesomorphy is positively associated with World Cup ranking. Hence, our data suggest that training should be aimed at a further increase of mesomorphy in male STS athletes.